2021
DOI: 10.1101/2021.08.26.21262649
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Behavioural barriers to COVID-19 testing in Australia: Two national surveys to identify barriers and estimate prevalence by health literacy level

Abstract: Background: COVID-19 testing and contact tracing has been crucial in Australia's prevention strategy. However, testing for COVID-19 is far from optimal, and behavioural barriers are unknown. Study 1 aimed to identify the range of barriers to testing. Study 2 aimed to estimate prevalence in a nationally relevant sample to target interventions. Methods: Study 1: National longitudinal COVID-19 survey from April-November 2020. Testing barriers were included in the June survey (n=1369). Open responses were coded us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…5 , 6 This study identified different top barriers to testing as in our previous Australia-wide survey in November 2020; although both observed concerns about the test being painful within the top five. 11 Conversely, we observed lower COVID-19 vaccine willingness in this study compared with national Australian estimates during similar time periods (53% vs. 68–73%), 5 , 6 although this rate was similar to a study of 199 people from NSW, Australia, who spoke a language other than English at home (58%), 27 and higher than a study of 516 Australian refugee and asylum seekers (28%). 27…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…5 , 6 This study identified different top barriers to testing as in our previous Australia-wide survey in November 2020; although both observed concerns about the test being painful within the top five. 11 Conversely, we observed lower COVID-19 vaccine willingness in this study compared with national Australian estimates during similar time periods (53% vs. 68–73%), 5 , 6 although this rate was similar to a study of 199 people from NSW, Australia, who spoke a language other than English at home (58%), 27 and higher than a study of 516 Australian refugee and asylum seekers (28%). 27…”
Section: Discussionsupporting
confidence: 61%
“…Participants were asked “ If I get signs of COVID-19 in the next 4 weeks (cough, sore throat, fever), the following might stop me from getting tested ,” with response options adapted from our previous survey findings, 11 , 22 modified to suit the Greater Western Sydney context (e.g., including responses that highlight concerns about visa status). Participants who responded “ I will get tested no matter what ” and listed no barriers were coded as high intention to get tested.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We recruited 1,526 Australian adults (430 men, 1064 women, 32 non-binary or not reported) for an online randomised study about COVID testing between October and November 2021 (www.anzctr.org.au/Trial/Registration/TrialReview.aspx?id=382318 ) using methods we have detailed previously 6 . We collected self-reported vaccination status (unvaccinated, 1 dose or 2 doses) and three measures of COVID-19 testing behaviour.…”
Section: Methodsmentioning
confidence: 99%
“…about COVID-19 testing between October and November 2021 (www.anzctr.org.au/Trial/Registration/TrialReview. aspx?id=382318) using methods we have detailed previously (6,7). We collected self-reported vaccination status (unvaccinated, one dose, or two doses) and three measures of COVID-19 testing behaviour: self-reported testing in past month or ever and intention to test if they woke with a sore throat.…”
mentioning
confidence: 99%